ETIKA KOMUNIKASI MAHASISWA TERHADAP DOSEN DALAM INTERAKSI AKADEMIK MELALUI MEDIA DIGITAL - Sudarto, Sudarto (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2024)
This research is survey research which aims to describe the form of communication ethics between students and lecturers in carrying out the academic interactions via digital media. The data collection technique used in this research is observation technique. The research instruments used were observation sheets and daily recording sheets. The data analysis technique used is descriptive data analysis technique. The results and conclusions: The worst communication ethics between the students in digital media towards the lecturers is "sending a message to the lecturer that he/she is sick, but there is no sick certificate from the doctor included" and followed by the ethic of "being slow to respond to the lecturer's message"; the best communication etiquette for students in digital media towards lecturers is to reply to the lecturer's message with the words "thank you, sir/ma'am" or "thank you, Puang" if you receive information from the lecturer as indicated, followed by the ethic of "replying "thank you." I'm back, sir/ma'am" if the lecturer sends a message saying "thank you. In general, it can be said that students' bad behavior in interacting with lecturers in digital media is still a cause for concern.